Auction failures and the market for auction rate securities - McConnell, John J.; Saretto, Alessio (Journal of Financial Economics, 2010)
The market for auction rate securities (ARS) made headlines during the second week of February 2008 when auctions at which the bonds’ interest rates reset experienced a wave of “failures.” Contrary to headlines that attribute the failures to a “frozen” market or investors’ “irrationality,” we find that (1) even at their height, less than 50% of ARS experienced auction failures, (2) the likelihood of auction failure was directly related to the level of the bonds’ “maximum auction rates,” (3) the implied market clearing yields of bonds with failed auctions were significantly above their maximum auction rates, and (4) ARS yields were generally higher than yields of various cash equivalent investment alternatives. We infer that investors priced the possibility of auctions failures into ARS yields and rationally declined to bid for bonds for which required market yields exceeded their maximum auction rates.